Translating the Sacred Text: A Suggested Model for Analyzing the English Translations of the Qur’an - Elnemr, Mahmoud Ibrahim Rezk (Journal of Posthumanism, 2025)
The aim of the current study is to offer a proposed integrative paradigm for analyzing Qur'anic translations into English. The research utilizes a systematic assessment model in examining key features, including the description of the unseen, reasons for revelation, categorization of chapters, readings of the Qur'an, abrogation, and translation of Allah's attributes. The Qur'an: A New Translation by Muhammad Abdel Haleem (2004) and The Clear Qur'an by Mustafa Khattab (2015) are the two translations in English of the Qur'an that were chosen to apply the suggested model. Findings also indicate that Abdel Haleem captures more precision in Qur'anic explanations, but neither of the translators properly explains causes of revelation or harmonizes differences in readings of the Qur'an. Both translators also possess slight variations in chapter classifications and neither of them provides explanation of the implication of abrogation, although Khattab provides more precise translations in certain instances. Both translations reflect strengths in the transmission of Allah's qualities but possess minor linguistic, cultural, and textual weaknesses. The study highlights how particular interpretive choices can influence the intended meaning and reception of the Qur'anic message by English readers. It further stresses the need for a translation model that includes both linguistic and legislative methodologies to ensure closer fidelity of the original text. By identifying the strengths and weaknesses of Khattab's and Abdel Haleem's translations, this study strengthens the current discourse on Qur'anic translation and proposes improvements to forthcoming books. It emphasizes contextual accuracy, methodological consistency, and adherence to classical Islamic learning in an attempt to enhance the quality of Qur'anic translations and better cater to readerships.